Development of Mobile-based Robotic Control for Real-Time Radiation Residue Monitoring System - Parthipan, Meenachi; Kian Sek, Tee (Evolution in Electrical and Electronic Engineering, 2021)
Radiation has many different forms and comes from many other sources in good term nor can be harmful to humans. Radiation congested environments importance to monitor regularly for minimize from risk. Although there is, exist many advance radiation-monitoring systems, but some human interaction during monitoring can direct exposure to radiation related disaster. Therefore, to avoid radiation related disaster due to direct exposure, a robot can replace human interaction during monitoring radiation. In this project, a mobile-based robotic control develops for real-time radiation residue monitoring system using Geiger-Muller Counter sensor. This sensor consists Geiger-Muller tube j305, which read radiation value in units of Counter Per Minutes (CPM) and micro Sievert per hour (uSv/h). A separate algorithm is implemented into this robot, which the robot control using android application and enable the user to monitor the radiation value on OLED display and Wi-Fi through display on graphical user interface. Therefore, a dashboard created using an Adafruit IO platform for analyzed the radiation value in real-time. The data can observe in unit term of Counter Per Minutes (CPM) and radiation dose in micro-Sievert per hour (uSv/h). The experiment conducted using tested with a harmless radiation contain material for analyzed the result. The threshold (CPM) value exceed makes an alert warning notification on dashboard in real-time.